Health-Related Quality of Life in leukemia Survivors of Allogeneic Hematopoietic Stem Cell Transplantation Employing the Mexican Reduced-Intensity Conditioning - González Ramírez, Mónica P.; Miravete Lagunes, Karla; Gómez de León, Andrés; Ponce de León, Sergio; Tenorio Rojo, Andrea P.; Martagón Herrera, Nora A.; Hérnandez Reyes, Jésus A.; García Villaseñor, Arturo; Burguette, Esteban; Vallejo Villalobos, María Fernanda; Ruiz Delgado, Guillermo José; Gómez Almaguer, David; et al. (Instituto Nacional de la Nutrición, 2015)
Background: Quality of life (QOL) is an important consideration in the counseling, implementation, and post-treatment management of arduous treatments for life-threatening conditions such as allogeneic hematopoietic cell transplantation (allo-HCT). Objective: To analyze the QOL of leukemia patients allografted with the Mexican reduced-intensity conditioning regimen in two Mexican academic medical centers. Material and methods: By means of the quality metric short form 36 version 2 to measure generic health concepts, relevant QOL was analyzed in leukemia patients who underwent allo-HCT using reducedintensity conditioning on an outpatient basis at either the Centro de Hematología y Medicina Interna de Puebla of the Clínica Ruiz or the Hematology Service of the Internal Medicine Department of the Hospital “Dr. José Eleuterio González” of the Universidad Autónoma de Nuevo León, and who had survived more than 12 months after the allograft, who could be approached, who were in a continued complete remission (with or without graft-versus-host disease), and who were willing to respond to the questionnaire. Thirty-five patients fulfilling these requirements were included, and a sex- and age-matched group of 35 reference subjects was also studied. Results: Allografted patients were found to have a slightly better mental component summary than the reference subjects (53.23 vs. 48.66 points; p = 0.01), whereas the physical component summary did not show a difference (54.53 vs. 52.05 points; p = 0.59). Most of the differences between allografted individuals and reference subject controls were not significant. Conclusions: Despite several sources of bias, these data suggest that allografted individuals employing the Mexican reduced-intensity conditioning regimen enjoy a health-related QOL life similar to that of reference subjects, adding another advantage of this method of conducting stem cell allografts. However, more work needs to be done to elucidate the impact of reduced-intensity conditioning on post allo-HCT QOL. (REV INVES CLIN. 2015;67:109-16) Corresponding author: Guillermo J. Ruiz-Argüelles, gruiz1@clinicaruiz.com